Management across cultures : insights from fiction and practice - Puffer, Sheila M. (Cambridge, Mass. : Blackwell Business, 1996)
This book contains three parts: Making Sense of the Cross-Cultural Experience, Managing Within Different Cultures, and Managing Globally Across Cultures.
Keywords: Business; Management; Management -- Cross-cultural studies; International business enterprises -- Management -- Social aspects; Intercultural communication